The Effectiveness of Covering in Increasing the Survival Rate of Vegetative Cuttings of Japanese Arborvitae (Platycladus orientalis L. Franco) with the Application of Growth Regulators - Sarwan, Elvira Hayu; Vauzia; Yuli Suprayitno (Microbiotech, 2026)
Vegetative propagation through cuttings is a commonly used method in the production of ornamental plant seedlings, including Platycladus orientalis (fan pine). The success rate of cuttings, particularly in terms of survival and rooting, is greatly influenced by microenvironmental conditions. The use of plant growth regulators (PGRs) in vegetative propagation of plants has been widely proven to enhance the effectiveness of adventitious root formation, particularly in woody plants such as the fan pine (Platycladus orientalis). This study aims to investigate the effect of cover type on the survival rate of fan pine shoot cuttings treated with the plant growth regulator (PGR) Rapid Root. This study employed a descriptive experimental method comparing two types of covers in the Rapid Root GR treatment. Two treatments were tested: the use of a large cover covering eight polybags simultaneously (total of 80 shoots) and a small cover covering one polybag each (total of 20 shoots). The results showed that the use of small covers yielded more optimal results, with a survival rate of 100%, an average of 6.1 roots per cutting, and no stem deaths. In contrast, the large cover only achieved a survival rate of 78.75%, with an average of 2.1 stem deaths per polybag and 4.5 roots per cutting. This difference indicates that small covers are able to create a more stable and controlled microenvironment, thereby supporting the growth and survival of cuttings more effectively. Therefore, the use of small covers is more recommended in the vegetative propagation system of fan palms using cutting and ZPT Rapid Root techniques.